1993
DOI: 10.1037/h0078856
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetries in the preparation and control of manual aiming movements.

Abstract: Two experiments were conducted to determine if typical right hand target aiming advantages could be reduced or eliminated by increasing the spatial demands of the aiming task. In Experiment 1, we found right hand advantages for both movement time and error regardless of spatial characteristics of the task. When we introduced a greater degree of spatial uncertainty in Experiment 2, subjects exhibited a left hand reaction time advantage. Taken together our results suggest that the right cerebral hemisphere may h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
51
0

Year Published

1995
1995
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(61 citation statements)
references
References 47 publications
10
51
0
Order By: Relevance
“…In contrast to feedback mechanisms, some authors have proposed a dominant arm/hemisphere advantage for movement planning, initiation, or sequencing (Annett et al 1979;Carson et al 1995;Todor and Kyprie 1980;Todor and Smiley-Oyen 1987). Other studies have suggested a nondominant arm/hemisphere advantage for movement preparation based on left-hand advantages in reaction time (Carson et al 1990;Elliott et al 1993). Thus the idea of differentiating dominant and nondominant arm control by open-or closed-loop control mechanisms alone remains controversial.…”
Section: Interlimb Differences In Open/closed-loop Processingmentioning
confidence: 92%
“…In contrast to feedback mechanisms, some authors have proposed a dominant arm/hemisphere advantage for movement planning, initiation, or sequencing (Annett et al 1979;Carson et al 1995;Todor and Kyprie 1980;Todor and Smiley-Oyen 1987). Other studies have suggested a nondominant arm/hemisphere advantage for movement preparation based on left-hand advantages in reaction time (Carson et al 1990;Elliott et al 1993). Thus the idea of differentiating dominant and nondominant arm control by open-or closed-loop control mechanisms alone remains controversial.…”
Section: Interlimb Differences In Open/closed-loop Processingmentioning
confidence: 92%
“…These differences between left-and right-handed reach-to-grasp actions are conspicuously absent in many previous grasping studies. Kinematic asymmetries favoring the dominant hand in reach-topoint actions are well documented (Boulinguez et al 2001a;Carson et al 1990Carson et al , 1993Elliott and Chua 1996;Elliott et al 1993;Fisk and Goodale 1985;Elliott 1986, 1989;Velay et al 2001), whereas multiple studies have demonstrated that manual asymmetries in the reach-to-grasp movement are subtle, if not altogether absent (Begliomini et al 2008;Flindall 2012;Flindall et al 2014;Grosskopf and Kuhtz-Buschbeck 2006;Tretriluxana et al 2008). The kinematic asymmetry recently identified during grasp-to-eat movements was interpreted as a right-hand/left-hemisphere advantage for eating, because participants produced smaller MGAs to eat while using their right hand only (Flindall and Gonzalez 2013).…”
Section: Discussionmentioning
confidence: 99%
“…However, studies demonstrating nondominant-arm advantages for reaction time [92][93] have proposed a nondominant specialization for movement preparation.…”
Section: Lateralization Of Motor Control Processesmentioning
confidence: 99%